Bone mass in prepubertal tennis players - Sanchis-Moysi, J.; Dorado, C.; Olmedillas, H.; Serrano-Sanchez, J. A.; Calbet, J. A. L. (International Journal of Sports Medicine, 2010)
To assess if exercise before puberty affects bone mineral content (BMC) and bone mineral density (BMD) we determined BMC and BMD in the dominant arm (DA) and non-dominant arm (NDA), lumbar spine and femoral neck in 25 tennis players (TP), 21 soccer players (SP) and 22 physically active controls (CG). All of them were under 12 years of age and prepubertal. In TP the DA was heavier than the NDA (7.5±0.8%), due to a greater lean mass (10.2±1.2%) and BMC (16.3±2.2%). The increased BMC is due to a greater DA bone area (11.1±1.9%) and BMD (4.1±0.7%). BMC inter-arm asymmetry was 50-75% of that previously observed in professional TP. Inter-arm asymmetry in lean mass, BMC, BMD and bone area was significantly higher in TP than in SP and CG. Lumbar spine BMC and BMD were similar across groups. TP and CG had similar femoral neck BMDs, whilst SP had higher femoral neck BMD than TP. In conclusion, tennis participation before puberty is associated with increased lean mass and bone mass, due to an enhanced bone size and areal BMD in the playing arm.